2016
DOI: 10.1175/jas-d-15-0332.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Surface Drag in Tornadogenesis within an Idealized Supercell Simulation

Abstract: To investigate the effect of surface drag on tornadogenesis, a pair of idealized simulations is conducted with 50-m horizontal grid spacing. In the first experiment (full-wind drag case), surface drag is applied to the full wind; in the second experiment (environmental drag case), drag is applied only to the background environmental wind, with storm-induced perturbations unaffected. The simulations are initialized using a thermal bubble within a horizontally homogeneous background environment that has reached … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 36 publications
5
66
0
Order By: Relevance
“…2)-the size and position of this grid were contain the Newcastle-Moore tornado and its parent storm to the best extent possible while remaining within the constraints of computational expense. Stretched vertical grid spacing is used, with a minimum vertical grid spacing of 20 m near the surface and an average vertical grid spacing of 340 m. Within the lowest kilometer above the surface, the average vertical grid spacing is 114 m. The smaller minimum vertical grid spacing at the surface than that of 500-m grid allows for better treatment of near surface processes, including frictionally generated vorticity that has been found to be important for tornadogenesis in our earlier studies (Schenkman et al 2014;Roberts et al 2016;Roberts and Xue 2017). Physics parameterization settings are the same as on the 500-m grid.…”
Section: Ensemble Design and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…2)-the size and position of this grid were contain the Newcastle-Moore tornado and its parent storm to the best extent possible while remaining within the constraints of computational expense. Stretched vertical grid spacing is used, with a minimum vertical grid spacing of 20 m near the surface and an average vertical grid spacing of 340 m. Within the lowest kilometer above the surface, the average vertical grid spacing is 114 m. The smaller minimum vertical grid spacing at the surface than that of 500-m grid allows for better treatment of near surface processes, including frictionally generated vorticity that has been found to be important for tornadogenesis in our earlier studies (Schenkman et al 2014;Roberts et al 2016;Roberts and Xue 2017). Physics parameterization settings are the same as on the 500-m grid.…”
Section: Ensemble Design and Methodologymentioning
confidence: 99%
“…Lerach et al (2008), another idealized simulation study, used 111-m grid spacing and focused on aerosol influences on tornadogenesis. More recently, the single-sounding-based simulation studies of Roberts et al (2016) and Roberts and Xue (2017) using a 50-m grid spacing examined the effects of surface drag and identified vorticity generated from surface drag as the primary source of vorticity for mesocyclone and tornadogenesis in their simulations. Hu and Xue (2007) and Xue et al (2014) were among the first studies to produce realistic forecasts of observed tornadoes-specifically, an F4 intensity tornado that occurred on 8 May 2003 in a supercell thunderstorm near Oklahoma City, Oklahoma.…”
Section: Introductionmentioning
confidence: 99%
“…This has been a hot topic in the severe storms community lately (Schenkman et al 2012(Schenkman et al , 2014Xu et al 2015;Roberts et al 2016) and unfortunately one that is exceptionally difficult to study both observationally and with simulations. Observational studies of the effects of surface friction are problematic because one cannot know how an observed storm might have behaved differently if in a frictionless setting.…”
Section: Aboveground Thermodynamic Observations In Convective Storms mentioning
confidence: 99%
“…The fact that the tornado formed about 10 minutes after the rapid intensification of the storm cell suggests that the tornadogenesis dynamics was different from that of supercell tornadoes, for which the downdraft and cold pool typically play important roles. Most likely, pre-existing vertical vorticity along the sea-breeze front (Roberts and Wilson, 1995), and possibly also the tilting of frictionally generated vorticity (Roberts et al, 2016), constituted the main sources of vorticity for the tornadogenesis, while the intense updraft accompanying the explosive storm development provided the intense low-level stretching for vortex intensification. The exact processes await further study.…”
Section: Wenchang Tornado (5 June 2016)mentioning
confidence: 99%
“…Because of the lack of precipitation before tornadogenesis, baroclinic vorticity generation could not have played an important role. The conceptual model of Wakimoto and Wilson (1989) for non-supercell tornadogenesis appears to apply here, while the conceptual model of Roberts et al (2016) on the role of surface friction in a rapidly developing tornado may also be applicable. The exact processes as well as the mesoscale environmental conditions for this tornado require further study.…”
Section: Zhanjiang Tornado (30 July 2016)mentioning
confidence: 99%